The German law of unjustified enrichment and restitution a comparative introduction - Dannemann, Gerhard (Oxford : Oxford University Press, 2009)
This text provides a comprehensive description in the English language of the German law of unjust enrichment, by explaining how this works in the context of German law, and by discussing the implications this would have if the German system were implemented in an English legal environment.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Unjust enrichment -- Germany; Restitution -- Germany